2018
DOI: 10.1177/0003319717753223
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in Giant Cell Arteritis: A Real-Life Retrospective Study

Abstract: This study aims to evaluate (1) the efficacy and safety of tocilizumab (TCZ) as a steroid-sparing agent in patients with giant cell arteritis (GCA) and (2) the usefulness of F-fluorodeoxyglucose positron emission tomography (FDG-PET) in the follow-up and to detect disease activity. We retrospectively evaluated 12 patients with GCA treated with TCZ (8 mg/kg/mo). Pre- and posttherapy data about clinical signs and symptoms, laboratory results, FDG-PET imaging study, and the mean glucocorticoid (GC) dose were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
11
0
2
Order By: Relevance
“…Τhe experience about temporal US in cranial GCA patients treated with TCZ is limited. Vitiello et al reported two cases in which initiation of TCZ treatment led to disappearance of ‘halo sign’ in the temporal US 4. In our clinic, TCZ resulted in significant amelioration of vessel wall inflammation in two cases.…”
supporting
confidence: 49%
“…Τhe experience about temporal US in cranial GCA patients treated with TCZ is limited. Vitiello et al reported two cases in which initiation of TCZ treatment led to disappearance of ‘halo sign’ in the temporal US 4. In our clinic, TCZ resulted in significant amelioration of vessel wall inflammation in two cases.…”
supporting
confidence: 49%
“…A further 42 articles were excluded following fulltext assessment. Eventually, 21 studies were selected for the qualitative analysis (systematic review) [16,17,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Eight studies were included in the meta-analysis since these reports contained sufficient data to either evaluate the accuracy of [18F]FDG-PET/CT for discriminating between active disease and remission during treatment [19,23,25,33] or to evaluate the proportion of patients in which the scan normalized during clinical remission in patients on treatment [17,20,22,36].…”
Section: Literature Searchmentioning
confidence: 99%
“…Few studies have examined FDG PET/CT as a potential imaging modality to monitor GCA disease activity in patients treated with corticosteroid-sparing therapies, such as anti-TNF and TCZ. In their retrospective study of 12 GCA patients treated with TCZ, Vitiello et al26 evaluated the value of FDG PET/CT in detecting and monitoring GCA disease activity. While patients were under low-dose corticosteroid therapy, a statistically significant reduction in FDG uptake was found, suggesting that FDG PET/CT may have the potential to monitor treatment response in TCZ-treated patients 26.…”
Section: Ancillary Diagnostic Methodsmentioning
confidence: 99%
“…In their retrospective study of 12 GCA patients treated with TCZ, Vitiello et al26 evaluated the value of FDG PET/CT in detecting and monitoring GCA disease activity. While patients were under low-dose corticosteroid therapy, a statistically significant reduction in FDG uptake was found, suggesting that FDG PET/CT may have the potential to monitor treatment response in TCZ-treated patients 26. Although the use of FDG PET/CT has promising implications, further prospective studies with larger sample sizes are required to determine the clinical significance of FDG PET/CT in the diagnosis and management of GCA.…”
Section: Ancillary Diagnostic Methodsmentioning
confidence: 99%